Menyoal Ketubuhan dan Nilai Performatifnya - F.X. Widaryanto (Dance and Theatre Review, 2019)
Corporeality as an existance of human body related to object and subject aroundis interesting to be explored, not only its capasity as an instrument of ritualpurposes but also as instrument of its daily “performative” expression. Thekinetic art is not considered belong to dance genre. It can be seen that the genreis expanded to be fluid so that one finds a difficulty to define performance stylewhich not convensionally has form patterns indicated by its kinetic genealogy.Through a profundity of the observation of human body motion related bothculturally and naturally to spatial “ecosystem,” one can see the performativevalue instead of its conventional performance characterized by the form ofits creative tradition. Furthermore, contemporarily it can be indicated thatcorporeality with performative values has a lot of opportunities to contributesignificantly within various aspects of ecocriticism. This is a kind of a critical thinking in term of an efford to remind everybody to be aware of the relationship between human and the environmental problems.Keywords: corporeality; ecocriticism; performative value